Social sector in a decentralised economy : India in the era of globalisation - Chakraborty, Pinaki; Chakraborty, Lekha S.; Mukherjee, Anit N. (Cambridge : Cambridge University Press, 2016)
This book is an analytical examination of financing and public service delivery challenges in a decentralized framework. It also provides critical insights into the effectiveness of public expenditure, through benefit incidence analysis of education and healthcare services in India. The benefits of decentralization always come with conflicts and trade-offs. By unpacking the process of decentralization, the authors identify that'unfunded mandates', arising from the asymmetry between finances and functions at local levels, are a major challenge. The analysis is carried out by distilling the existing studies in this area, and through an empirical investigation of public finance data at different public sector levels in India, as well as in some selected developing countries. Using the household survey statistics of consumption expenditure, an analysis of utilization or benefit incidence of public spending on social sectors in India is achieved, covering education and health sectors.
Title from publisher's bibliographic system (viewed on 29 Sep 2017).
Keywords: Decentralization in government -- Economic aspects -- India; Intergovernmental fiscal relations -- India; Revenue sharing -- India; Human services -- India -- Finance; Education -- India -- Finance; Public health -- India -- Finance